2022
DOI: 10.1007/s10822-022-00461-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HPr kinase/phosphorylase inhibitors: novel antimicrobials against resistant Enterococcus faecalis

Abstract: Enterococcus faecalis, a gram-positive bacterium, is among the most common nosocomial pathogens due to its limited susceptibility to antibiotics and its reservoir of the genes coding for virulence factors. Bacterial enzymes such as kinases and phosphorylases play important roles in diverse functions of a bacterial cell and, thus, are potential antibacterial drug targets. In Gram-positive bacteria, HPr Kinase/Phosphorylase (HPrK/P), a bifunctional enzyme is involved in the regulation of carbon catabolite repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Kinases are crucial for bacterial growth, biofilm formation, and antibiotic resistance. Recent studies have reported the important role of penicillin-binding protein and serine/threonine kinase-associated (PASTA) kinases in regulating resistance to β-lactam antibiotics 40 , 41 . Hence, bacterial kinases have received considerable attention as prospective targets for the discovery of novel antimicrobial agents 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinases are crucial for bacterial growth, biofilm formation, and antibiotic resistance. Recent studies have reported the important role of penicillin-binding protein and serine/threonine kinase-associated (PASTA) kinases in regulating resistance to β-lactam antibiotics 40 , 41 . Hence, bacterial kinases have received considerable attention as prospective targets for the discovery of novel antimicrobial agents 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the important role of penicillin-binding protein and serine/threonine kinase-associated (PASTA) kinases in regulating resistance to β-lactam antibiotics 40 , 41 . Hence, bacterial kinases have received considerable attention as prospective targets for the discovery of novel antimicrobial agents 40 . Interestingly, animal strains uniquely contained histidine kinase (cssS, maeK, dcuS_2, and dcuS) and HPr kinase/phosphorylase (HPrK/P) proteins (isolates code no.…”
Section: Discussionmentioning
confidence: 99%